"Fibre Bragg Grating": Measurement of the deflection of the ski board using this method - Nakajima, H.; Yoshioka, S.; Harada, M.; Hakamada, T.; Inaba, Y.; Murayama, H.; Kimura, A.; Ishige, Y. (Journal of High Performance Sport, 2024)
Ski deflection plays a vital role in determining the quality of the carving turn and overall skiing performance. Therefore, it is essential to quantify the ski deflection accurately. Prior research has utilized strain gauges to investigate ski deflection, but this method posed challenges, including difficulties in measuring the multiple points of the ski. To address these limitations, we focused on utilizing Fiber Bragg Grating (FBG), a technology that can effectively resolve these issues, and developed new techniques to investigate ski deflection. Furthermore, we employed this method to quantify the ski deflection during the carving turn for sit-skier, identifying their areas of improvement to enhance the skiing performance. This paper presents the verification tests of ski deflection using FBG, as well as the technical issues encountered by sit-skiers. Firstly, we conducted a laboratory test to confirm if the FBG strain sensor could detect ski deflection when weights were suspended. Secondly, we conducted an on-snow test to determine if the FBG strain sensor could detect the ski deflection during a straight downhill ski run, with forward and backward loads. The results of these verification tests validated FBG's ability to measure ski deflection. Subsequently, we compared the ski deflection of a sit-skier with that of a standing skier during a carving turn. We found that the sit-skier had difficulty deflecting the forebody of the ski, which limited the range of carving turn techniques sit-skier could perform compared with the standing skier. For instance, fine adjustments in turn radius during carving turns are restricted. In summary, our study demonstrates the potential of FBG to measure ski deflection at multiple points accurately, providing detailed insights for skiers, unlike the strain gauge. Thus, we anticipate that FBG will become a common technique for measuring ski deflection in the future.